2014
DOI: 10.2147/ijwh.s64431
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-acting reversible contraceptive use, teenage pregnancy, and abortion rates in England

Abstract: BackgroundSince the late 1990s, the British government has launched major strategies to address high teenage pregnancy and abortion rates in England. These have focused in part on improving access to contraception through national campaigns. This study assessed teenage pregnancy and abortion rate trends since 1998 and possible associations with usage of long-acting reversible contraceptives (LARCs).MethodsTeenage conception rates and age-specific abortion rates were obtained from the Office for National Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Prior counselling on future fertility was also associated with being on LTPM. This finding was in agreement with the South African study, 10 which showed higher chances of being on LTPM for mothers who had prior counselling on future fertility. Consequently, there is a need for broader counselling in post-partum mothers to include their future fertility intentions and all contraceptives available to reduce unintended pregnancy rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Prior counselling on future fertility was also associated with being on LTPM. This finding was in agreement with the South African study, 10 which showed higher chances of being on LTPM for mothers who had prior counselling on future fertility. Consequently, there is a need for broader counselling in post-partum mothers to include their future fertility intentions and all contraceptives available to reduce unintended pregnancy rates.…”
Section: Discussionsupporting
confidence: 92%
“… 5 A study in England showed a decrease in unintended pregnancies between 1998 and 2011, and a statistically significant association between the decrease and the use of LTPM was found. 10 In 2012, the American College of Obstetricians and Gynaecologists recommended the use of LTPM for all women. 11 These methods are safe, non-user-dependent and have the highest continuation rates compared with other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers finding a strong association between falling teenage pregnancy rates and increasing use of long-acting reversible contraception in England since the late 1990s have underlined the contribution of increased access to reliable contraception to the decline. 17 Observers in the USA have reached similar conclusions 18 supported by intervention studies examining the effect of providing highly effective contraception free of charge. 19 By contrast, researchers using ecological analyses of routinely collected area-level data in England to examine the association between educational attainment, contraceptive use, and trends in conception in women younger than 18 years concluded that the larger association with education indicates that this is the key driver.…”
Section: Discussionmentioning
confidence: 80%
“…The strong and sustained association between conception in women younger than 18 years and earlier sexual activity suggests that sizeable additional gains might also be made by helping young women to become sexually active at a time that is right for them. 27 A third of all young women, and 60% of those for whom first sex occurs before age 16 years, subsequently consider that to have been too early for them. Bringing actual timing of first sexual encounter in line with preference for timing of first sexual encounter could cut teenage pregnancy rates further, and an intensified policy focus aimed at achieving this might be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers projected that if the CHOICE model was adopted nationally among all sexually active teens in the U.S., the pregnancy rate of 67.8 per 1,000 teens (in 2008) [ 33 ] could be reduced to 29.6. [ 33 , 34 ] Confirmation of this assertion was a recent paper showing reductions in teenage pregnancy and abortion rates in England as LARC usage increases [ 35 ].…”
Section: Introductionmentioning
confidence: 93%